Analysis of the Impact of Liquidity and Adequacy of Operational Cash Flow on the Detection of Financial Distress Risk in Retail Companies Listed on the Indonesian Stock Exchange - H Hanifah (Universitas Pendidikan Indonesia, 2023)
The research investigates liquidity conditions and operational cash flow adequacy in retail companies listed on the IDX from 2016 to 2022, aiming to detect the risk of financial distress. Employing a descriptive and verification method, secondary data from annual financial reports were analyzed using logistic regression in SPSS. The findings reveal that, on average, the companies exhibit sufficient liquidity and operational cash adequacy. While financial distress is generally deemed safe, caution is warranted as values are above 0. The study establishes that liquidity and operational cash flow adequacy significantly impact the detection of financial distress, explaining 78.6% of the variance. Notably, 21.4% remains influenced by other factors. This underscores the importance of considering liquidity and cash flow when assessing a company's risk of financial distress. The implications for theory and policy suggest using these metrics as preemptive tools for companies, prompting the establishment of minimum standard liquidity and cash flow policies. Additionally, recommendations include creating standardized policies for receivables and inventory turnover, with key performance indicators (KPIs) for the receivables department. The research's novelty lies in the collaborative analysis of liquidity and operational cash flow adequacy as independent variables, focusing on retail companies listed on the IDX from 2016 to 2022. The utilization of logistic regression enhances the accuracy of the resulting model. These insights contribute to a more comprehensive understanding of the factors influencing financial distress in the retail sector, offering practical implications for management and policy formulation.